Ecologic zonation model of the benthic foraminifera and thecamoebians of Guadiana river estuary and application in paleoenvironmental reconstruction - Camacho, Sarita (2012)
This thesis explores the potential of benthic foraminifera as environmental indicators in the Guadiana River estuary according to an actual perspective, where we study the species distribution patterns and their responses to seasonal environmental changes and a paleoenvironmental perspective, in which the previous information in combination with the knowledge of diagenetic processes is applied in interpreting analogues environments that formed in the estuary during the Holocene. The variation of environmental parameters in the estuary showed strong dependence on spatial and seasonal gradients, exhibiting prevailing river conditions in winter and marine conditions in summer. The distribution of foraminifera in the Guadiana estuary mirrored the seasonal variation of environmental factors, whose relative importance depended on the proximity the tolerance limits of the species. The elevation proved to be the most important parameter in the distribution of foraminifera by combining the effect of a series of other variables. Based on the dominant species of living foraminifera and seasonal variations in their relations was possible to define a model of ecological zonation for the Guadiana estuary. Four biocenoses were identified and compared with the fraction of dead and fossil foraminifera. The total assemblage that combines the seasonal and taphonomic effects on modern microfaunas proved to represent reliably the estuary indigenous microfauna. Its application in the interpretation of paleoenvironments recorded over two sedimentary sequences (CM3 and CM5) allowed refining the knowledge on how the estuary has evolved over the past 13 000 cal yr BP. The pioneering study of communities of thecamoebian and tintinnids suggests that both groups are an asset in studies of environmental monitoring and paleoenvironmental reconstruction. The present work demonstrated that the three indicators analyzed, when integrated in a multi-proxy perspective, increase the potential interpretive which can be applied in paleoenvironmental reconstructions.